Penerapan Asas Contradictoire Delimitatie dalam Pelaksanaan Pendaftaran Tanah di Kabupaten Biak Numfor - Konstantina Renyaan (Kyadiren, 2021)
This study aims to examine the implementation of the Contradictoire Delimitatie principle in the first land registration and the elements that hinder the use of the Contradictoire Delimitatie guideline in the implementation of land registration especially in Biak Numfor. This type of research is an empirical juridical research. The research was carried out at the National Land Agency (BPN) of Biak Numfor Regency. Data were provided through related document review, observation and interviews with related officers. The research data were then analyzed descriptively. The results confirm 1) the application of Contradictoire Delmitatie in determining the land boundaries during registration process at Biak’s BPN has not gone well. The parties are required to show their existing land boundaries either signs or stakes. 2) The factors that inhibit Contradictoire Delmitatie principle related to land boundary determination during the registration process are land boundary discrepancies, boundary stakes that cause unclear land, the absence of the parties during land boundary determination